MARKET RETURN, VOLATILITY AND TRADING VOLUME DYNAMICS AFTER ECONOMIC CRISIS - Djohanputro, Bramantyo (Journal of Indonesian Economy and Business, 2011)
This paper attempts to explore the relationships of return â trading volume and volatilityÂ â trading volume. Trading volume may represent a proxy of information, liquidity, andmomentum. The up and down of trading volume, therefore, contain certain informationÂ that can be extracted by traders to make investment decision. Regressions of market returnon its lags, volume, and conditional variance and regressions of volatility on its lags,Â volume, and conditional variance are employed. Traders may respond positive informationdifferently from negative information. To accommodate such behaviour, threshold autoregressiveÂ conditional heteroskedasticity or TARCH is employed. Using market data ofÂ Indonesia Stock Exchange between economic crisis and before sub-prime mortgage crisisÂ (from year 2000 to 2007) indicate the existence of return â volume relationships as well asÂ volatility â return relationships albeit not very strong. There is also an indication thatÂ traders respond positive information differently from negative information concerningreturn movements but there is no indication concerning volatility movements.Keywords: return, volatility, volume, TARCH